Cellular Angiofibroma of Vagina Presenting with Secondary Infertility - Bharti, Jyotsna Naresh (Avicenna Research Institute, 2014)
BACKGROUND: Cellular angiofibroma, first described in 1997, is known to occur in both genders with equal predilection occurring in middle aged females and older males. CASE PRESENTATION: In this study, a case of vaginal cellular angiofibroma was reported in a 30 year old female presenting with secondary infertility. The case was diagnosed based on morphology and immunohistochemistry and was treated surgically. The interesting feature of the case was the rarity of its incidence at the vagina and its resemblance to other benign and more aggressive tumours in the same site. CONCLUSION: Cellular angiofibromas are benign tumours, which rarely occur in vagina. Although middle aged females are affected more, cellular angiofibromas can affect females of reproductive age group and can cause secondary infertility. These tu-mours need to be distinguished from other benign tumours and aggressive tumours occurring in the same site.